Pencegahan Tindakan Perundungan pada Lingkungan Sekolah Dasar - Sunandari Sunandari; Fitriani Fitriani; Nurannisa Nurannisa; Muh Dzul Ikram; Windini Maharani (Departement of Mathematics Education, 2023)
This article uses a qualitative research method, which means the author only uses the theory of journals or books as references in the sources or references used in writing articles. The aim of qualitative research is to build knowledge through understanding based on complex pictures, detailed reports and scrutinizing words and their theoretical foundations focus on factual research. This bullying is selected and given to elementary school students which aims as a preventive measure to prevent bullying in the school environment. Because school is a place of learning where students should have a comfortable, safe and quiet place to study, not learning that is filled with anxiety, fear and insecurity because of bullying by their friends. Based on the results of the research, it can be concluded that prevention of bullying (1). Participate in enforcing school rules related to bullying, (2). Support each other against bullies (3). Report to the teacher or homeroom teacher regarding acts of bullying, (4). Dare to tell parents, (5). Seek support from other friends, (6). Don't reply to people who bully, (7). Help and defend friends who are victims